The side effects of platinum-based chemotherapy drugs: a review for chemists. Issue 19 (10th April 2018) - Oun, Rabbab; Moussa, Yvonne E.; Wheate, Nial J.
Abstract : The platinum chemotherapy drugs cisplatin, carboplatin, and oxaliplatin are known to cause seven different types of side effects in patients. Abstract : The platinum-based drugs cisplatin, carboplatin and oxaliplatin are regularly prescribed in the treatment of cancer and while they are effective, their use is limited by their severe, dose-limiting side effects (also referred to as adverse effects/events). In total, a cancer patient can experience any combination of around 40 specific side effects. The dose-limiting side effect for cisplatin is nephrotoxicity, for carboplatin it is myelosuppression, and for oxaliplatin it is neurotoxicity. Other common side effects include anaphylaxis, cytopenias (including leukopenia and neutropenia, thrombocytopenia, and anaemia), hepatotoxicity, ototoxicity, cardiotoxicity, nausea and vomiting, diarrhea, mucositis, stomatitis, pain, alopecia, anorexia, cachexia, and asthenia. The side effects may require patients to be prescribed dose reductions in their platinum drugs of between 25 and 100%. Furthermore, patients require extensive monitoring of their biochemistries, kidney and liver function, and depending on the drug, hearing tests. Finally, patients are commonly co-prescribed additional non-chemotherapy based drugs to treat the side effects which can include antiemetics, antibiotics and myeloid growth factors, mannitol, propafenone, saline hyperhydration, magnesium supplements, monoclonal antibody cytokine blockers, and antioxidants.